Does jumping to the beat result in better ratings from gymnastics experts? - Veit, F.; Riedel, L.; Jeraj, D. (Journal of Human Sport & Exercise, 2022)
How does auditory information influence the perception and evaluation of complex skills? Especially in technical compositional sports, such as gymnastics, the visual information perceived by the judges (and coaches) is the subject of an immediate evaluation. Various factors influence the judges` performances. The impact of auditory information on the evaluation of complex skills is predominantly unexplored. Therefore, the study aimed to investigate floor music`s role in female gymnastics routines. Participants with different gymnastics expertise were asked to rate acrobatic series on the floor in three different audio-visual conditions (original, inter-beat, matched-beat). The current study results show that participants (irrespective of the group) rated acrobatic series in the matched-beat higher than in the original condition. In conclusion, it would be interesting to investigate if an effect on the participants` perception is given for other gymnastics skills (gymnastic jumps and leaps) or the overall (execution) score on the floor.